Spatial analysis of multidimensional poverty in Colombia: Applications of the Unsatisfied Basic Needs (UBN) Index - Álvaro Turriago-Hoyos; William Andrés Martínez Mateus; Ulf Thoene (Cogent Economics & Finance, 2020)
This research article seeks to specify and measure the determinants of multidimensional poverty in Colombia using the Unsatisfied Basic Needs (UBN) Index based on information from the latest available 2005 population census applying a spatial econometric approach. An exploratory analysis of the spatial distribution of the UBN and a confirmatory analysis through spatial models are conducted using municipalities as the unit of analysis. This spatial analysis confirms diffusion effects of poverty between neighbouring municipalities, the existence of clusters and hot spots in the Pacific Chocó region, the Caribbean Coast, and the southern region of the country. Within those clusters, we find high levels of unemployment, low levels of urban population, as well as a high proportion of ethnic minorities, and large size municipalities. This research contributes to public policymaking and the improvement of governance in the third largest Latin American country by population size and the region's fourth largest economy.
Keywords: 330; Colombia; multidimensional poverty; new economic geography; socio-economic development; spatial econometrics; unsatisfied basic needs index